Production of superlight saraline drill-in fluid - Muhammad, B.M.Y.; Abdul Raman, Abdul Aziz (2011)
Fragmental rock accumulates around the perforation channel and the permeability of this zone decreases during drilling. Underbalanced drilling cleans the perforation channel and increases oil production. A superlight Saraline drill-in fluid produces a pressure differential. Glass bubbles (GB) were used to reduce the density of this fluid. The required viscosity and stability of the fluid were maintained by adding homogenizing and stabilizing agents. Laboratory tests showed that the density of the fluid with a Saraline: GB mass ratio of 60:40 and a homogenizing and stabilizing agent content of 3 and 9 wt. can be 500 kg/m(3), i.e., much lower than the density of pure Saraline, 722.2 kg/m(3).